2000
DOI: 10.1159/000064844
|View full text |Cite
|
Sign up to set email alerts
|

Is Systematic Sextant Biopsy Suitable for the Detection of Clinically Significant Prostate Cancer?

Abstract: Background: The optimal extent of the prostate biopsy remains controversial. There is a need to avoid detection of insignificant cancer but not to miss significant and curable tumors. In alternative treatments of prostate cancer, repeated sextant biopsies are used to estimate the response. The aim of this study was to investigate the reliability of a repeated systematic sextant biopsy as the standard biopsy technique in patients with significant tumors which are being considered for curative treatment. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 11 publications
(18 reference statements)
0
5
0
2
Order By: Relevance
“…It is possible that some prostate cancer cases have remained undetected among the patients included in the group of noncancer diagnosis. However, all biopsies were obtained using a scheme of 12-14 cores, making false-negative results less likely than with the historical sextant biopsy protocol (Manseck et al, 2000). Furthermore, all participants were followed according to the routines established in the hospital, and those with a subsequent cancer diagnosis, within a 6-month period, were reclassified as cancer patients, minimizing misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that some prostate cancer cases have remained undetected among the patients included in the group of noncancer diagnosis. However, all biopsies were obtained using a scheme of 12-14 cores, making false-negative results less likely than with the historical sextant biopsy protocol (Manseck et al, 2000). Furthermore, all participants were followed according to the routines established in the hospital, and those with a subsequent cancer diagnosis, within a 6-month period, were reclassified as cancer patients, minimizing misclassification.…”
Section: Discussionmentioning
confidence: 99%
“…As long as the cancer can't be detected by all these perturbed needle positions, it is regarded as being missed by the th needle in the optimization framework. Accordingly, the probability function in (1) is reformulated by replacing with , which is defined as (3) where is the number of random perturbation cases considered. Note that this is a very strict definition, which requires that, for a tentative needle configuration, if cancer is detected, cancer is also present in the vicinity of the needles.…”
Section: B Atlas-based Biopsy Optimizationmentioning
confidence: 99%
“…The most popular sampling method has been the sextant biopsy [2], which divides the left and right parts of the prostate into three regions each, then randomly samples each of them. This approach has been shown to have a large false negative detection rate ranging from 27% to 39%, depending on cancer stage [3], [4]. For example, the study in [5] showed that 23% of initially positive sextant biopsies were followed by a negative repeat biopsy, indicating the significant error of the technique.…”
mentioning
confidence: 99%
“…In most biopsy procedures, the sampling locations are determined in a random or empirical manner, leading to mis-detection of cancer and mis-estimation of surrogate markers [30, 14]. To cope with that, several computer-assisted approaches (e.g., [45, 42, 49]) have been developed.…”
Section: Introductionmentioning
confidence: 99%